The Influence of Media Innovation Application Suno AI Song Animals on Creativity Ability in Children Aged 5-6 Years - Wardani, Dzikrina Revitania; Fachurrazi, Ahmad (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2025)
Early childhood is the period of the best abilities between the ages of 0-6 years, which experiences abilities and growth by providing educational stimulation that covers all aspects of the child's abilities. to prepare for further education. Suno AI Application Innovation Media Animal Songs on Creativity in Children Aged 5-6 Years The songs are designed to meet the various characteristics of early childhood, especially the unique, active and energetic, explorative and adventurous characters, and cognitive abilities in children aged 4-6 years. Media Innovation Application Suno AI Animal Songs on Creativity in Children Aged 5-6 Years Animal songs are a means to stimulate children's cognitive abilities in critical thinking and high imagination. Therefore, researchers conducted quantitative research using experimental methods and design. non-equivalent or